2015
DOI: 10.1589/jpts.27.2407
|View full text |Cite
|
Sign up to set email alerts
|

Ankle inversion taping using kinesiology tape for treating medial ankle sprain in an amateur soccer player

Abstract: [Purpose] The purpose of this study was to report the effects of ankle inversion taping using kinesiology tape in a patient with a medial ankle sprain. [Subject] A 28-year-old amateur soccer player suffered a Grade 2 medial ankle sprain during a match. [Methods] Ankle inversion taping was applied to the sprained ankle every day for 2 months. [Results] His symptoms were reduced after ankle inversion taping application for 2 months. The self-reported function score, the reach distances in the Star Excursion Bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…In addition, the sprained ankle was protected from reinjury through the mechanical effects of AET application. Previous studies have reported that kinesiology tape application to an ankle with instability 10 ) and eversion sprain 11 ) reduced pain and improved stability. Therefore, healing of ankle inversion sprain was possible.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the sprained ankle was protected from reinjury through the mechanical effects of AET application. Previous studies have reported that kinesiology tape application to an ankle with instability 10 ) and eversion sprain 11 ) reduced pain and improved stability. Therefore, healing of ankle inversion sprain was possible.…”
Section: Discussionmentioning
confidence: 99%
“…The application of elastic therapeutic tape used in this study is known to have a mechanical corrective effect on malalignment of the pelvis [9] and shoulder, [8] in addition to preventing injuries [10] and alleviating pain [6,7,11,12] and increasing lymphatic circulation. [13] Although there were differences with the present study in the method and duration of tape application, Jeon et al [14] reported that applying kinesiology tape 15 times in 4 weeks for patients with moderate hallux valgus effectively reduced the HVA from 21.95° to 18.74°.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The balance taping was removed within 24 hours and reapplied every day, regardless of the presence or absence of skin itching. [6,7] As a result, there was no skin irritation or other adverse event.…”
Section: Case Reportmentioning
confidence: 97%
“…The findings of our study agree with those of the previous literature: the highest incidence of ankle sprains occurred in team sports that involve contact between players (American football, Australian football, field hockey, Gaelic football, lacrosse, rugby, and soccer). 14 We did not examine other factors related to deltoid ligament sprains that may increase (eg, previous injury history) 2,6,8 or reduce (eg, taping and bracing techniques, 15,16 shoe design, 17 teamspecific strengthening programming) injury risk. Future investigators should evaluate these potential injury risk factors and prevention strategies.…”
Section: Incidencementioning
confidence: 99%